CRENÇAS DOCENTES ACERCA DO PAPEL DAS HUMANIDADES NA FORMAÇÃO DO BACHAREL EM DIREITO - Barbosa, Lidiane Locateli (2024)
The present study presents as its central focus of study the beliefs of teachers of two Law majors regarding the importance of teaching humanities in the formation of the bachelor. In the search for understanding the relationship between higher education teaching practice and their perceptions, the following problem was outlined as an investigation: what are the beliefs of legal professionals, as professors, about the importance of teaching humanities in the formation of legal professionals? To answer the question, the general objective was presented: analyzing the beliefs of Law professionals, as professors, about the importance of teaching humanities in the formation of Law professionals. The research is justified by exposing issues related to the need to operationalize the teaching of humanities in legal majors, offering reflections on the possibility and necessity, and, at the same time, the difficulty of rescuing the legal knowledge that privileges the construction of autonomy, critical thinking, producing reflective, creative, conscious, productive beings, capable of modifying their historical-cultural-socioeconomic context. The methodology adopted was exploratory, descriptive research with a qualitative approach. Four professors, with degree in Law, Masters, with more than ten years of teaching, members of the NDE of Law majors at two community universities in the interior of the State of Rio Grande do Sul were constituted as research subjects. questionnaires answered on Google Forms and recorded and manually transcribed interviews were presented, which were later analyzed in the perspective of the Appraisal Theory, one of the discursive semantic systems of Systemic-Functional Linguistics, in its attitude subsystem, promoting revealing results about the intentions of the researched professors expressed in their speeches, therein resides the ideology present in their speeches, consistent in their beliefs, highlighted from the lexico-grammatical elements which were analyzed. In conclusion, the beliefs of the professors participating in the research converge in the sense that the teaching of humanities is very important in the formation of law graduates, based on ethics and criticality.